Explaining the National Cultural Distance Paradox - Brouthers, Keith D.; Brouthers, Lance Eliot (Journal of International Business Studies, 2001)
Past studies of the relationship between national cultural distance and entry mode choice have produced conflicting results. Some scholars find cultural distance associated with choosing wholly owned modes; others find cultural distance linked to a preference for joint ventures. In this paper we provide both theoretical and empirical evidence to explain the discrepant findings and thus, help to resolve the national cultural distance paradox.